Diseño de una metodología para la integración entre los actuantes de la red de valor de ciclo cerrado basado en los perfiles psicológicos y estilos de liderazgo (2019)
Research is a tool to find effective solutions to the integration failures between the participant agents in the closed cycle value network through the design of a methodology based on psychological profiles and leadership styles. The objective is to allow the participant agents to integrate its key processes in order to help the network operability, thus achieving an economic, social and environmental benefit. In order to achieve this, the first step is the collection of information in secondary specialized sources such as scientific articles, books, theses, among others. This is done to identify the reasons behind organizations not considering psychological profiles and leadership styles in the management processes, which could correspond to the design of the methodology.